Relevansi Keterlibatan Milineal dalam HRD - Khairunnisa, Nabilah; Farah, Amelia; Ibkar, Nazal; Anshori, Mochammad Isa (RIGGS: Journal of Artificial Intelligence and Digital Business, 2026)
Millennials now dominate the workforce, prompting Human Resource Development (HRD) to adapt strategically to their needs and expectations. This article reviews national and international literature on millennial involvement in HRD. Millennials value work flexibility, self-development, work-life balance, transparency, collaboration, and digital technology. Literature shows their involvement fosters a collaborative, digital, and innovative work culture and shifts HRD from administrative to strategic, employee-focused practices. Challenges include high turnover, low long-term loyalty, and rising demands for recognition and well-being. Effective HRD strategies should include digital training, tailored reward systems, and participatory leadership to boost engagement, productivity, and commitment. Millennial involvement is therefore essential for organizational sustainability and competitiveness in the digital era.